Game-Based Learning in Enhancing Learning Motivation - Sugianto, Hendi (Universitas Nurul Jadid Probolinggo, Indonesia, 2023)
This study aims to explore the effectiveness of game-based learning (GBL) in enhancing student motivation at MTs Darul Falah. The research utilizes a qualitative approach to assess the impact of GBL on student engagement and motivation through indicators such as active involvement, value awareness, long-term commitment, and positive behavioral changes. Data were collected through in-depth interviews with teachers and students, as well as classroom observations. The findings indicate that GBL is effective in creating an immersive learning experience, increasing student engagement, and fostering sustained learning motivation. The implementation of GBL not only deepens students' understanding of the subject matter but also fosters positive attitudes and commitment towards learning. This research enriches the literature by providing new insights into how game elements can be used to motivate and improve student learning outcomes.